All under heaven : the Tianxia system for a possible world order - Zhao, Tingyang (Great transformations, 2021)
"In this succinct yet ample work, Zhao Tingyang as one of China's most distinguished and respected intellectuals, provides a profoundly original philosophical interpretation of China's story. Over the past few decades, the question "where did China come from?" has absorbed the thoughts of many of China's best historians. Zhao, keenly aware of the persistent and pernicious asymmetry in the prevailing way scholars have gone about theorizing China according to Western concepts and categories, has tasked both Chinese and Western scholars alike to "rethink China." To this end, Zhao introduces what he terms a distinctively Chinese centripetal "whirlpool" model of world order to interpret the historical progression of China's "All-Under-Heaven" Tianxia identity construction on the central plain of China. In this book, Zhao forwards a novel and compelling thesis on not only how we should understand China, but also until recently, how China has understood itself"--